Effect of energy input on flocculation process and flotation performance of fine scheelite using sodium oleate. (October 2017) - Chen, Wei; Feng, Qiming; Zhang, Guofan; Li, Longfei; Jin, Saizhen
Highlights: Flocculation process of fine scheelite using sodium oleate was studied. Size distribution and shape of flocs as a function of energy input were measured. Flocculation process of different size fractions less than 10 µm was analyzed. Suitable energy input in shear-flocculation was flocculation process dependent. Abstract: We have investigated the effect of energy input on the flocculation process and flotation behavior of fine scheelite of less than 10 µm size. Sodium oleate was used as a dual-function reagent, acting as flocculant and collector. Energy input in shear flocculation was controlled in a four-baffle cylindrical tank with a four-blade impeller by changing the agitation speed. The flocculation process was investigated by measuring continuous transformations in size distribution and observing floc shape. The results show that with increasing energy input, the size distribution of fine scheelite transforms from unimodal to bimodal. The flocs produced tend to possess more branches with low energy input and tends to become globule-like with high energy input. A parameter termed the flocculation degree was introduced to quantify the flocculation process as a function of energy input. The flocculation degree with increasing energy input reveals the aggregation order of different size fractions (all less than 10 µm) when forming flocs. The flotation rate of flocs formed with different energy input was studied. The results demonstrate that the flotation rate is closely related to energy input and also, exhibits an intimate correlation with flocculation degree. These results could potentially be used to routinely monitor the flotation performance of fine particles in operating plants when shear flocculation is used.